Optimal design of viscoelastic damping structures using layerwise finite element analysis and multi-objective genetic algorithm. (September 2015) - Xu, Chao; Lin, Song; Yang, Yunzhao
Highlights: Multi-objective optimization method is proposed to design viscoelastic structures. Layerwise finite element analysis is used to model multilayer damping structures. NSGA-II with parallel computation is applied as optimization algorithm. Simultaneous material layout and geometry optimization are achieved. Abstract: An optimization method for design of viscoelastic damping structures is presented. The optimal design problem is formulated as a multi-objective constrained optimization problem. A plate finite element based on the layerwise theory is applied to simplify modeling and optimization process. A modified reference point based non-dominated sorting genetic algorithm with parallel computation is used as optimization algorithm. The effectiveness of the approach is verified by numerical applications. It is shown that simultaneous material layout and geometry optimization can be achieved by combining the advantages of the layerwise finite element analysis and multi-objective genetic optimization, and the method is computationally efficient.